FAKTOR-FAKTOR YANG MEMPENGARUHI KESEJAHTERAAN PETANI ROSELLA MELALUI CORPORATE SOCIAL RESPONCIBILTY - Ferliansyah Zais; Umi Khulsum; Meilia Risna; Shinta Ayu Purnamasari (LPPM Politeknik Pratama, 2023)
The purpose of this study was to investigate the factors that influence the welfare of rosella farmers through corporate social responsibility (CSR) activities. The factors investigated were digital literacy, simple bookkeeping, and Islamic business ethics. The location of the study was at PT. Tanah Harapan Wisata Alam (Hopeland Camp) in Cipelang Village, Bogor Regency, West Java Province. Qualitative research methods were used to guide this study. The findings revealed that of the three factors investigated, digital literacy had the most real impact on Rosella farmers. Digital literacy helps Rosella farmers access knowledge about modern agricultural technology, find new product innovations, and seek access to funding and wider market access. The simple bookkeeping they use helps them to record expenses and income obtained to then be shared with the company. The practice of Islamic business ethics is used as a basis for behaving in holding the mandate and responsibility in managing the company's Rosella land. The principles of justice ('adl) and profit sharing (mudharabah) have been carried out so far, and provide a high sense of trust between farmers and company owners. It can be concluded that all three factors have a role in supporting farmers to improve their economy.